Missional worship, worshipful mission : gathering as God's people, going out in God's name - Meyers, Ruth A., 1957- (Grand Rapids, MI. Wm. B. Eerdmans Publishing Company., 2014)
Too many Christians still think that worship is only a Sunday-morning activity done inside the church, while mission involves how the church engages the outside world. But Ruth Meyers argues that a dynamic relationship exists between worship and mission -- that gathering as God's people includes at its heart our being sent out into the world in God's name. Meyers explores this relationship by taking readers through the various parts of the worship service: gathering, proclaiming the Word, praying for the world, celebrating the Eucharist, and going forth to continue participating in God's mission in the world. In each chapter Meyers includes stories of worship practices in different churches and considers how the actions of worship relate integrally to mission. Missional Worship, Worshipful Mission emphasizes that missional worship is not a set of techniques but rather an approach to worship and congregational life in which God's mission permeates every aspect of what the church does.
Imagining missional worship -- Gathering in the name of God -- Proclaiming and responding to the word of God -- Praying for the world -- Enacting reconciliation -- Celebrating the communion meal -- Going forth in the name of Christ -- Preparing missional worship -- Concluding reflections: Missional worship as work for the common good.
Includes bibliographical references (pages 240-242).
Keywords: Worship; Missions -- Theory; Common good -- Religious aspects -- Christianity